The efficacy of amino acids on regeneration and analysis of genetic fidelity of regenerated Chrysanthemum morifolium cv. Zembla / Sharifah Aina Afzan Syed Aminud-Din - Sharifah Aina Afzan , Syed Aminud-Din (2021)
Tissue culture technique has been widely applied for the propagation of Chrysanthemum morifolium, a high value ornamental plant. However, somaclonal variation is the biggest challenge for tissue culture industry due to generation of “off-types” plants. This study aims to investigate the effects of supplements in order to improve callus and shoot induction media composition and evaluate the clonal fidelity in regenerated plantlets using retrotransposon-based markers. Leaves and nodal explant materials of Chrysanthemum morifolium “Zembla” were used for callus induction on Murashige and Skoog (MS) media containing 30 g L-1 sucrose, 2 g L-1 gelrite, 3 mg L-1 benzylaminopurine (BAP), 1 mg L-1 naphthaleneacetic acid (NAA) supplemented with amino acids (glutamine and arginine) and casein hydrolysate at concentrations of 250, 500 and 750 mg L-1. Addition of amino acids and casein hydrolysate individually to the media showed no significant effect in callus induction efficiency. However, arginine (500 and 750 mg L-1) and casein hydrolysate (500 mg L-1) individually produced the highest number of shoots (4.6-4.8 shoots per explant) in calli induced from the nodal explants. Shoots with calli induced from leaf and nodal explants were transferred to elongation media. Elongation media supplemented with glutamine (750 mg L-1) produced the highest number of shoots at 1 cm within 4 weeks (1.4 shoots per explants) when nodal explants were used. Thirty regenerants of Chrysanthemum morifolium “Zembla”, (17 plants of white flower variety, and 13 plants of yellow flower variety,) were assessed for their genetic variation using Inter Retrotransposon Amplified Polymorphism (IRAP) marker. Out of nine primer combinations, only Sukkula primer was able to produce clear IRAP banding pattern in Chrysanthemum morifolium. Sukkula primer was able to differentiate between the white and yellow variants of Chrysanthemum morifolium “Zembla”. Furthermore, IRAP revealed polymorphic bands within the varieties. White and yellow flower varieties showed 20.0 % and 15.4% genetic variations, respectively. Further analysis is needed to confirm the linkage between these genetic variations and somaclonal variations.